Estudo numérico, implementação computacional e verificação experimental do fenômeno da fuga térmica em materiais viscoelásticos - Rodovalho, Luiz Fernando Ferreira (2014)
This work is dedicated to the development of a strategy for numerical-computational modeling and experimental verification of the self-heating phenomenon in viscoelastic materials with emphasis on the thermal runaway phenomenon taking into account the combined effects of dynamic loads and static preloads. The methodology of modeling by finite element allows us to consider the influence of frequency, temperature and static preload on the self-heating phenomenon of the linear viscoelastic materials. For this purpose, modifications are made that allow thermomechanical analysis of more complex viscoelastic structures, in addition the evaluation of introducing metal inserts in bulk material for reducing effects of self-heating. The validation of the proposed model and the identification of the physical parameters of thermal efficiency and heat transfer by natural convection, initially unknown, are obtained by comparison of the results of numerical simulations with the corresponding obtained through experimental tests for a specimen formed by a translational viscoelastic joint. The curve-fitting procedure is formulated as an inverse optimization problem through use of the Firefly Algorithm for minimizing the objective function defined as the square difference between the temperatures obtained from the simulations and the corresponding generated by the tests for each time instant. The accuracy and limitations of the model are evaluated by comparing the experimental and simulated temperature profile, allowing to verify the numerical evidence and the qualitative consistence of the results obtained with reported in the literature for the thermal runaway phenomenon for simple devices without effect preload.